2015
DOI: 10.3390/ijfs3040530
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Governance Elements on Corporate Social Responsibility (CSR) Disclosure: An Empirical Evidence from Listed Companies at KSE Pakistan

Abstract: Abstract:The purpose of this study is to investigate the potential effects of corporate governance (CG) elements on corporate social responsibility (CSR) disclosure. The annual reports of companies for the year [2007][2008][2009][2010][2011] are examined to analyze the relationship between CG and CSR reporting. It considers the elements of CG such as board size, independent directors, foreign nationalities and women representation in the board, ownership concentration, institutional ownership, firm size and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
137
4
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(222 citation statements)
references
References 50 publications
23
137
4
17
Order By: Relevance
“…Management should not only be aware of the CSR reporting costs, but also of the positive link to firm reputation and stakeholder trust, which could lead to better CSR and financial performance in the long run. However, involvement in CSR practices may not generally be transformed into CSR reporting (Majeed et al, 2015). Insofar, firms without CSR reporting can be active in CSR management and may plan to introduce a CSR report in future.…”
Section: Limitations and Recommendations For Further Researchmentioning
confidence: 99%
“…Management should not only be aware of the CSR reporting costs, but also of the positive link to firm reputation and stakeholder trust, which could lead to better CSR and financial performance in the long run. However, involvement in CSR practices may not generally be transformed into CSR reporting (Majeed et al, 2015). Insofar, firms without CSR reporting can be active in CSR management and may plan to introduce a CSR report in future.…”
Section: Limitations and Recommendations For Further Researchmentioning
confidence: 99%
“…As a result, the barriers to the development of environmental accounting would be addressed primarily by the Malaysian government and authorities. Majeed et al (2015) investigated factors affecting the level of disclosure of information about environmental and social responsibility of listed firms in Pakistan. The study was conducted with a sample of 49 firms with annual reports from 2007 to 2011.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results revealed that those companies which did not practice CSR avoided the obligation of tax payments. Moreover, the companies that did not practice CSR had an aggressive attitude towards the responsibility of paying taxes (Khan, Yousaf, Khan, & Yasir, 2014) Literature reveals that the potential impacts of Corporate Governance (CG) components on CSR disclosure were examined (Majeed, Aziz, & Saleem, 2015). The yearly reports of organizations for the year 2007-2011 were inspected to investigate the relationship between CG and CSR reporting.…”
Section: Chronological Picturementioning
confidence: 99%